Concentration Polarization of Ox-LDL and Its Effect on Cell Proliferation and Apoptosis in Human Endothelial Cells - Liu, Shijie; Mehta, Jawahar L; Fan, Yubo; Deng, Xiaoyan; Ding, Zufeng (Journal of Cardiology and Cardiovascular Medicine, 2016)
Background: Flow-dependent concentration polarization of native LDL is important in the localization of atherogenesis. However, ox-LDL plays a more important role than n-LDL in atherogenesis by inducing cell proliferation and apoptosis. We hypothesized that concentration polarization of ox-LDL may adversely affect vascular beds due to its toxicity to endothelial cell (EC) lining. Methods: Using a parallel-plate flow chamber technique, we studied water filtration rate and wall concentration of ox-LDLs EC monolayers cultured on permeable or non-permeable membranes. ECs cultured on permeable and non-permeable membranes were examined in terms of cell viability, ox-LDL uptake, LOX-1 expression and cell apoptosis (Cytochrome c and Bcl-2 expression). We observed that the wall concentration of ox-LDL was about 16% higher in the permeable group than in the permeable group (P<0.05). Cell proliferation (MTT assay) increased in response to low concentration of ox-LDL (1-5 μg/ml), and fell drastically in response to higher concentration; all these changes were more pronounced in the permeable group than in the non-permeable group. The uptake of ox-LDL and LOX-1 expression by ECs were also significantly higher in the permeable group than in the non-permeable group of cultured cells. Conclusions: These observations suggest that concentration polarization of ox-LDL occurs in an artery that is permeable to water, and ox-LDL concentration polarization can enhance ox-LDL accumulation into the arterial wall and accelerate EC proliferation at low concentrations and apoptosis at high concentrations, possibly via LOX-1 expression.